Wireless Sensor Network for Environmental Monitoring: Application in a Coffee Factory. (26th December 2011) - Valverde, J.; Rosello, V.; Mujica, G.; Portilla, J.; Uriarte, A.; Riesgo, T.
Abstract : Wireless sensor networks have been a big promise during the last few years, but a lack of real applications makes difficult the establishment of this technology. In this paper a real monitoring application in an instant coffee factory is presented. This application belongs to the group of environmental solutions based on wireless sensor networks, and it is focused on the impact of the instant coffee production processes in one of the largest instant coffee factories in Europe. The paper includes the entire application scenario, from the hardware of the WSN nodes to the software that will evaluate the impact and will close the loop.